Experimental investigations on heat and mass transfer performances of a liquid desiccant cooling and dehumidification system - Ou, Xianhua (2020)
The last decades have witnessed the growth interest in Liquid Desiccant Dehumidification Systems (LDDS). In the conventional LDDS, the high dilution rate of desiccant solution in dehumidifier leads to a high desiccant regeneration frequency, which consequently results in more thermal energy consumed by desiccant regeneration system. Therefore, a more energy efficient Liquid Desiccant Cooling and Dehumidification (LDCD) system is developed in this study, which mainly composes of a cooling coil and dehumidifier. A simple static model is proposed to predict the performances of heat and mass transfer process in this system. The thermal efficiency, moisture effectiveness and desiccant dilution rate are utilized as the performance indicators. The influences of several relevant parameters on the cooling and dehumidification performances of LDCD system are investigated. The model predictions are compared with the experimental data, and the results show that the model predictions are well in line with the experimental data with the maximum errors less than 10%. Moreover, the feasibility of LDCD system in reducing the dilution rate of desiccant solution and the system energy consumption is validated. The results indicate that the dilution rate of desiccant solution and energy consumption of the LDCD system are reduced by 39.64% and 22.3% over the conventional LDDS, respectively.